TITIAN JALAN MENUJU SURGA - Moh Isa Anshary Muta’al (Jurnal Studi Agama, 2018)
Paradise and its bliss is the highest reward of God for His faithful servants. It is the highest demand of every human being for the duration of his life in his day and nights. And what God has prepared from Paradise and its bliss to its all that exists in this world of His creation. All religions have claimed its existence, but Islam has made it one of the pillars of faith, which is only accessible to those who are blessed by God with His mercy. It was repelled in his way by those who disbelieved in it. They said, “This is only the myths of the first.”